2001
DOI: 10.1080/09638280150211284
|View full text |Cite
|
Sign up to set email alerts
|

Stroke rehabilitation: application and analysis of the modified Barthel index in an Arab community

Abstract: We conclude that MBI is simple, convenient, efficient, gives exact and accurate information about daily activities and ambulation and could be used in inpatient follow up sittings, in the Arab and culturally similar Middle East countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Participants who had had a stroke in the past tended to chose HR as they had previously learned that the event was not too severe; perhaps they also learned that an institutional setting did not provide an intensive treatment and that most of the time they were idle (Keith, 1988). The tendency of Arabic patients to choose HR (which was not statistically significant) may be explained by their cultural background, which determines that when individuals have a disability they should be among family and be cared for by relatives (Azzali, 2001). A longer stay in the acute-care hospital for patients in the IR group does not necessarily indicate a more severe condition but could partly be explained by the need to wait for an available bed in the rehabilitation institution.…”
Section: Discussionmentioning
confidence: 96%
“…Participants who had had a stroke in the past tended to chose HR as they had previously learned that the event was not too severe; perhaps they also learned that an institutional setting did not provide an intensive treatment and that most of the time they were idle (Keith, 1988). The tendency of Arabic patients to choose HR (which was not statistically significant) may be explained by their cultural background, which determines that when individuals have a disability they should be among family and be cared for by relatives (Azzali, 2001). A longer stay in the acute-care hospital for patients in the IR group does not necessarily indicate a more severe condition but could partly be explained by the need to wait for an available bed in the rehabilitation institution.…”
Section: Discussionmentioning
confidence: 96%
“…It demonstrates good reliability and validity in a variety of settings and with a variety of patients. 2,12,[50][51][52][53][54][55][56][57] Gresham et al 58 found the BI to be more complete, sensitive to change, and familiar than the Katz Index of ADL and the Kenney Self Care Evaluation. The BI also has shown concurrent validity with the Rivermead Mobility Index, Nottingham Extended ADL Scale, Frenchay Activities Index, Rankin Scale, Katz Index of ADL, Kenney Self Care Evaluation, and PULSES Profile.…”
Section: Topics In Geriatric Rehabilitationmentioning
confidence: 99%
“…1,2 Forty-five percent of all Medicare dollars in the United States are spent on rehabilitation of patients with stroke. 1 Stroke obviously presents a physical and economic burden to the patient, caregiver, and society as a whole.…”
mentioning
confidence: 99%
“…Each category is scored according to the performance of the patient in performing the tasks independently, with some help or in a dependent manner and results in a total score that can range from 0 to 100 or can be scored in intervals that reflect the degree of dependency of the patients for daily living activities [9,11,12]. Cultural adaptation of the MBI was performed and validated for Brazil in 2004, and the instrument may help to prevent or delay the onset of disability [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It was originally developed to monitor the performance of patients hospitalized for an extended time, with paralysis conditions before and after treatment, and to indicate the medical care necessary for such patients [8]. Due to its ease and speed of application, the MBI is now used as an evaluation instrument for neurological and musculoskeletal disorders and to predict hospitalization time, prognostics and consequences of discharge [9].…”
Section: Introductionmentioning
confidence: 99%